Developing a Framework for Evaluating Ethical Outcomes of Good Participatory Practices in TB Clinical Drug Trials. (July 2016) - MacQueen, Kathleen M.; Eley, Natalie T.; Frick, Mike; Mingote, Laia Ruiz; Chou, Alicia; Seidel, Stephanie S.; Hannah, Stacey; Hamilton, Carol
Good Participatory Practice Guidelines for TB Drug Trials (GPP-TB) were issued in 2012, based on similar guidelines for HIV prevention and reflecting growing acceptance of the importance of community engagement and participatory strategies in clinical research. Though the need for such strategies is clear, evaluation of the benefits and burdens are needed. Working with a diverse group of global TB stakeholders including advocates, scientists, and ethicists, we used a Theory of Change approach to develop an evaluation framework for GPP-TB that includes a clearly defined ethical goal, a set of powerful strategies derived from GPP-TB practices for achieving the goal, and outcomes connecting strategies to goal. The framework is a first step in systematically evaluating participatory research in clinical trials.